2018
DOI: 10.9734/cjast/2018/45855
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Flowering and Fruiting Behaviour in Some Important Cultivars of Mango (Mangifera indica L.)

Abstract: Flowering and fruiting behaviour studied in five important cultivars of mango viz. Langra, Bombai, Zardalu, Bangalora and Hemsagar. The bud break, the appearance of 50% flower in panicle and fruit set was noticed in different time among the cultivars. The flowering intensity (%), the percentage of hermaphrodite flower (%), inflorescence shape and colour, inflorescence length and breadth (cm) significantly differed among the cultivars. The fruiting behaviour like fruit set (%), fruit drop (%), number of fruits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The variation in length of panicles in mango varieties might be due to genetic composition and more specifically the physiological condition of the shoot on which panicle arise. These results are also in harmony with findings obtained by Azam et al (2018), Kumar et al (2018), Kishor et al (2019), and Indian et al (2020).…”
Section: Panicle Studysupporting
confidence: 92%
“…The variation in length of panicles in mango varieties might be due to genetic composition and more specifically the physiological condition of the shoot on which panicle arise. These results are also in harmony with findings obtained by Azam et al (2018), Kumar et al (2018), Kishor et al (2019), and Indian et al (2020).…”
Section: Panicle Studysupporting
confidence: 92%
“…The variation of panicle colour in the present experiment is also due to the variation of their genotypic characters. Kumar et al (2018) has also reported pinkish green, greenish pink, light green and light pink colour in various mango varieties.…”
Section: Colour Of Paniclementioning
confidence: 89%
“…Urban agriculture has become a popular activity in big cities all over the world [5][6][7], especially after experiencing the Covid-19 pandemic [8][9][10].…”
Section: Introductionmentioning
confidence: 99%